FAMILY INTERVENTIONS TO DEAL WITH PSYCHO SOCIAL PROBLEMS OF CARETAKERS OF PERSONS LIVING WITH CANCER – CASE STUDY - Rasquinha, Shwetha; Shekhar, Rameela (International Journal of Research -GRANTHAALAYAH, 2021)
Family has a central role at the time of crisis. When an individual suffers with terminal illness like Cancer it definitely becomes more supportive. But in a crisisful situation like such, the family requires supportive interventions. This article presents a case study of primary caretaker of a cancer patient who undergoes severe psycho social challenges. Aim of this paper is to highlight the need and effectiveness of family intervention by Medical Social Worker through a case study. Psycho education to family, team work, utilizing the resources has shown remarkable results in reducing the psycho social problems of caretaker. Family environment plays a very significant role in psycho social support of its members. Positive environment and family socialization experiences enhances one’s ability to cope with stress and anxiety. Hence family interventions for caretakers of persons living with cancer can support both care givers and patients. Multidisciplinary approach in cancer care is the need of the hour. It can build a proper support mechanism for the person suffering from cancer and his family. The most important implication of the current study is the unveiling of the need for Medical Social Workers in oncology settings and the interventions they can deliver. A professionally trained medical Social Worker, equipped with psycho social skills to work with caretakers, patients and their families can be a effective oncology Social Worker